Desarrollo y validación del método analítico por espectrofotometría para la cuantificación de mebendazol suspensión - Gutiérrez Castro, Jhemifer Paola (2008)
In the present study parameters for validation of analytical method spectrophotometric to quantifying Mebendazole Suspension was carried. We performed an analysis of Mebendazole 100 mg/5ml Suspension, lot 00202027 (Instituto Quimioterápico S.A. - IQFARMA). Formic acid were used as solvents and isopropyl alcohol. The method used in this report proved to be selective in determining the analyte between the excipients, the samples were subjected to degradation by UV getting 99,932% for the sample and radiated 100,016% for non-irradiated sample. The test Linearity introduced a correlation coefficient of 0.9998; Test Statistical Linearity and Response Factor, expressed conformity. For the study of Accuracy, the percentage of recovery was 100736. In Test G Cochran was lower than G Experimental Tables (0,4315 <0,8709). For statistical Student t test was smaller than t Experimental Table (1,861 <2,306), so that the accuracy is correct according to their specifications. In assessing the accuracy, repeatability of the test showed a concentration averaged 99,917 mg/5ml a CV% of 0,467. The intermediate Accuracy In the coefficient of variation between the average values of an analyst and the other was 1,480%, being acceptable for validation. The parameters allow certain validation as validated analytical method TPT077 to review 06 proposed by the laboratory Instituto Quimioterápico S.A. (IQFARMA), for quantifying Mebendazole Suspension